Pelos caminhos do aprendizado: limites e possibilidades da relação professora/criança em tempos de pandemia - Tanabe, Cristiane Ryu Jordão (2023)
This study has as research object the pedagogical practices applied in face-to-face post- pandemic teaching. It is based on sources of a bibliographic and documental nature, with a field research having been carried out with the participation of ten teachers who work in the Elementary School of the Initial Years of municipal public schools in the State of São Paulo and who answered a questionnaire through the Google forms. Its objective is, through the analysis of the teaching practices of the professionals, to verify whether there have been changes due to the pandemic and the return to face-to-face teaching. The pandemic demanded reflection on the ways in which teaching is arranged, on the possibility of teaching children without the support of the school environment: would they learn outside of school? And, after returning to school, is it possible to return to previous practices? Faced with these questions, the hypothesis arises that dialogue favors development and can be strategic for learning to occur. Theoretical references are based on the three principles of complex thinking by Edgar Morin, in addition to his recent work on the coronavirus, there are several works by other authors who have addressed this subject: Santos (2020) and Harari (2020). We used the works of Paulo Freire referring to the use of dialogue and context for learning. Along this route, it was observed that the period of social isolation demanded the use of conversation as a way to soften the experiences brought by the children, as they expressed the need to talk about the events they witnessed and had repercussions on their behavior in the classroom. This situation directed the pedagogical work of the teachers who, touched, rethought their practices to better serve the children when they returned to school, as they saw that it was necessary to listen to them in order to continue with their learning. The reflection showed them that the conversation would be the way to do this, it was also thought to foresee spaces destined for their use in the planning. The opening to the conversation proved to be a promising path that is close to the one that Freire (2019, 2011 and 2013a) took with the literacy students, as he saw in dialogue a means of getting to know better the reality of those involved and then meeting their learning needs. Freire (2011) reveals that it is through the student's speech that one learns to dialogue with him and together knowledge regarding life is built.